EFEKTIVITAS PENGGUNAAN MEDIA BERGAMBAR DALAM PENGAJARAN ILMU TAJWID PADA SISWA KELAS V MADRASAH IBTIDAIYAH ASRORUL HUDA BEKASI - Mursalih Mursalih; Moch. Hasyim Fanirin (Bajang Institute, 2022)
That many factors determine the success or failure of a learning process, including the method used by the teacher. Methods that have been used and considered to be good may turn out to be less effective than current methods in line with the development of science and technology. Thus it is necessary to constantly evaluate the methods used in the learning process at all levels of education and teaching. This study aims to determine the effectiveness of the use of pictorial media in teaching Tajweed science to fifth grade students of Madrasah Ibtidaiyah. This study uses a quantitative approach with correlation test analysis in order to determine the degree of relationship between the objects of this study are the fifth grade students of Madrasah Ibtidaiyah Asrorul Huda Bekasi in 2020. Data collection techniques use interviews, documentation. The results of statistical tests in Alpha 0.05 show that the hypothesis (H0) is rejected, meaning that there is a difference between the values before using pictorial media and after using pictorial media. The increase in value can be seen in: (1) the fluency value of students in reading recitation, and (2) the value of understanding the meaning of the science of recitation; Thus the use of pictorial media by teachers of the process of teaching tajwid to fifth grade students of Madrasah Ibtidaiyah Asrorul Huda Bekasi will contribute to improving student learning outcomes, especially in tajwid.